Deposition of PTFE thin films by RF plasma sputtering on < 100 > silicon substrates - Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Polymers have been studied extensively due to the wonderful array of properties presented by them. Polymer materials can be coated/deposited by various techniques like sputtering (magnetron, ion beam, RF or dc), plasma polymerization, etc. and can be used in coatings, paint industries, etc. The present study deals with the RF sputter deposition of poly(tetrafluoro ethylene) (PTFE), commonly known as Teflon. Depositions were carried out on mirror polished silicon (1 0 0) substrates at different powers in the range of 100-200 W. The deposition time was kept constant at 60 min. The sputtered film shows lower contact angle of 50&DEG; with water and 44&DEG; with diiodomethane, a lower interfacial tension value of 0.76 dyne/cm, indicating hydrophilicity and good adhesion of the film with the substrate. FHR indicates presence of C-F, C-F-2 bonding groups in the deposited film. Further, XPS study shows presence of CF3 (292.2 eV), CF2 (290.8 eV), C-F (288.0 eV) and C-CF (286.4 eV) moieties indicating deposition of PTFE films at higher power levels of plasma. © 2004 Elsevier B.V. All rights reserved.
Keywords: Contact angle measurement; FTIR; PTFE; RF plasma sputtering; XPS

Electron beam induced surface cross-linking of functional monomers coated on silicon substrate - Mahapatra, S. K.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A.; Bhoraskar, Vasant N. (Materials Letters, 2006)
A 3: 1 composition of functional monomer: multifunctional acrylate was spin coated and later cross-linked under the influence of keV electron irradiation on the surface of silicon to generate a surface-anchored cross-linked network bearing functional moieties. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) as well as wetting angle measurements were used for the analysis of functional monomer cross-linked surfaces. Results of the surface reconstruction of surfaces and electron irradiated on coated silicon wafers reveal that long-term hydrophilic surfaces can be achieved. Thus, the surface architecture can be favorably manipulated by using this remarkable technique with a Suitable combination of functional monomers and cross-linkers. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: electron beam irradiation; FTIR; Polymers; surface modification; XPS